Implicações das avaliações em Larga Escala nas Práticas Pedagógicas: Perspectivas dos Professores da Rede Municipal de Ensino de Foz do Iguaçu (2011-2017) - Bernardino, Maria do Rosário Flôr (2019)
The present research has as object of the Larrge Scale Evaluations, and seeks to identify the possible implications of Prova Brasil in the educacion of the municipal network of Foz do Iguaçu/PR. from 2011 to 2017. Since 2011, the municipality of Foz do Iguaçu has been implementing policies and strategies for large-scale evaluations, seeking to improve IDEB, and nationally as a scholl system, with each edition. Some of these strategies influence and/ or modify the pedagogical practices, interfering in the teaching -learning process. Our analysis aims to investigate the implications of Large-Scale. Assessments on pedagogical practices, from the perspective of teachers in the municipality of Foz do Iguaçu in fifth-grade classes. The methodological course started from a qualitative research with literature review, document analysis and field research including the application of questionnaires to teachers of the municipal school system in five municipal schools located in different regions of the city. As results, we can see that the teachers of the municipal network of Foz do Iguaçu consider that there is an influence of IDEB/Prova Brasil in their pedagogical practices.It was also found that there is no specific training for large-scale assessments in the municipality, but that both SMED and schools undertake focused actions on assessments, and that some of these result in bonuses as an incentive for students, and Furthermore, according to the teachers, there is a priority in teaching the subjects of Portuguese and Mathematics in IDEB/Prova Brasil, in fifth year classes, with the anticipation of the contents in the first there quarters of the year